Behavioral factors on investment Behavior Analysis of In active Algeria Banks - Oum Elkheir RAMDANI; Mohamed lamine CHERBI (Journal of Excellence for Economics and Management Research, 2020)
This study deals with the impact of behavioral factors in the decision-making process of investors. The study aims to study the most important psychological and behavioral aspects of the clients and to determine the extent of the behavioral financial interpretation in this aspect. The study relied on analyzing the opinions of a sample of commercial banks' clients, Financial and investment decisions and transactions.     The study concluded that all of the rationality, attitudes and confidence in the financial market were affected by the behavior of the traders in the direction of investment decisions and that the financial market is efficient and transparent in providing information whenever the investor's behavior is rational.     Finally, the study recommended that the importance of transparency of data and credibility of financial transactions effect on the behavior of clients in terms of rationality should be strengthened.